COVID-19 outbreak and CO₂ emissions: Macro-financial linkages - Julien Chevallier (Journal of Risk and Financial Management, 2021)
In the Dynamic Conditional Correlation with Mixed Data Sampling (DCC-MIDAS) framework, we scrutinize the correlations between the macro-financial environment and CO2 emissions in the aftermath of the COVID-19 diffusion. The main original idea is that the economy's lock-down will alleviate part of the greenhouse gases' burden that human activity induces on the environment. We capture the time-varying correlations between U.S. COVID-19 confirmed cases, deaths, and recovered cases that were recorded by the Johns Hopkins Coronavirus Center, on the one hand; U.S. Total Industrial Production Index and Total Fossil Fuels CO2 emissions from the U.S. Energy Information Administration on the other hand. High-frequency data for U.S. stock markets are included with five-minute realized volatility from the Oxford-Man Institute of Quantitative Finance. The DCC-MIDAS approach indicates that COVID-19 confirmed cases and deaths negatively influence the macro-financial variables and CO2 emissions. We quantify the time-varying correlations of CO2 emissions with either COVID-19 confirmed cases or COVID-19 deaths to sharply decrease by -;15% to -30%. The main takeaway is that we track correlations and reveal a recessionary outlook against the background of the pandemic.
Keywords: 330; COVID-19; CO2 emissions; time-varying correlations; macroeconomy; stock markets; DCC MIDAS